Civilizational Imperatives : Americans, Moros, and the Colonial World - Charbonneau, Oliver, 1984- (Book collections on Project MUSE., 2020)
"This book reveals the little-known story of how the United States colonized and governed Southeast Asian Muslim territories in the early twentieth century"--